2022
DOI: 10.1177/20406207221081637
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of salvage intensive chemotherapy versus venetoclax-combined regimen in patients with relapsed/refractory acute myeloid leukemia (AML)

Abstract: Background: Evidence that a venetoclax (VEN)-combined regimen is effective in relapsed/refractory acute myeloid leukemia (R/R AML) is emerging. However, it is unknown how VEN-combined low intensity treatment compares to intensive chemotherapy (IC) in medically fit patients with R/R AML. Methods: We compared AML patients who received IC ( n = 89) to those who received a VEN in combination with hypomethylating agents or low dose cytarabine (VEN combination) ( n = 54) as their first- or second-line salvage after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 63 publications
(101 reference statements)
2
16
0
Order By: Relevance
“…The DEC + VEN group received the same daily dose of DEC for five days combined with 28 days of VEN (400 mg daily) per cycle. The cycle 1 ramp-up, disease response evaluation, VEN dose reduction in concomitant with azoles, and the resting period between cycles were the same as in the VIALE-A trial [ 11 , 14 , 15 ]. We induced cytoreduction of white blood cell (WBC) counts <20 × 10 9 /L by hydroxyurea, low-dose intravenous cytarabine, or leukapheresis before DEC or DEC + VEN treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEC + VEN group received the same daily dose of DEC for five days combined with 28 days of VEN (400 mg daily) per cycle. The cycle 1 ramp-up, disease response evaluation, VEN dose reduction in concomitant with azoles, and the resting period between cycles were the same as in the VIALE-A trial [ 11 , 14 , 15 ]. We induced cytoreduction of white blood cell (WBC) counts <20 × 10 9 /L by hydroxyurea, low-dose intravenous cytarabine, or leukapheresis before DEC or DEC + VEN treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Uric acid reducing agents (allopurinol, febuxostat, or rasburicase) and intravenous fluid hydration were administered for the prevention of tumor lysis syndrome. We used fluconazole 400 mg/day during the neutropenic period in all patients as antifungal prophylaxis without antibacterial prophylaxis [ 14 , 15 ]. DEC and DEC + VEN treatments were maintained until disease progression, a severe adverse event, a hematopoietic stem cell transplantation (HSCT), or the patient requested discontinuation.…”
Section: Methodsmentioning
confidence: 99%
“…Through data mining FAERS, the new and rare AEs can be evaluated and detected. Compared with the previous clinical studies on VEN [18][19][20][21], this study was based on a large sample size and a long time span, and found new AE signals, filling the gap in the study of VEN related AEs in the real world. It is of great significance to understand the safety of VEN.…”
Section: Discussionmentioning
confidence: 97%
“…Our research results also show that off-label use accounts for 12.2% (2,339/19,107) of the total number of reports, which indicates that off-label use seems to be very common in clinical use of VEN. The AML is the most indication, accounting for more than 1/3, CLL is close to 1/3, and the remaining 1/3 are currently unapproved indications [ 20 , 21 , 42 ]. Although off-label use gives patients hope and some efficacy, it also brings a higher risk of AEs than conventional use, which requires careful evaluation and treatment by clinicians [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the approval for use is currently confined to patients with ND-AML, mounting evidence indicates increasing off-label use of these combinations to treat refractory/relapsed (R/R) AML because of their efficacy and safety profile. According to a series of reports [ 7 , 8 , 9 , 10 ], VEN-HMA combinations have yielded response rates as high as 64% in R/R-AML patients [ 8 ], which appears to be noninferior to results with salvage IC [ 10 ], even though the treatment intensity of the VEN combination is much lower than that of conventional cytotoxic salvage regimens.…”
Section: Introductionmentioning
confidence: 99%